Pengelolaan Makanan Khas Ranau (Kue Gelang) Melalui Ibu PKK Dalam Pengenalan Budaya Di Kecamatan Buay Pematang Ribu Ranau Tengah - Putri , Selin Monica; Murdiati , Eni; Isnaini , Mohd Aji (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Bracelet cakes are one of the long-lasting snacks if stored properly, namely in a jar or other airtight container, as a treat for guests or a family snack. Bracelet cakes shaped like donuts with a sweet aroma from brown sugar are the creativity of making pastries. The creativity highlighted in this bracelet cake is in terms of its unique shape, which resembles a bracelet and tastes so sweet. The purpose of making this thesis entitled "Management of Typical Ranau Food (Bracelet Cake) Through Mrs. PKK in Introduction to Culture in Buay Pematang Ribu Ranau Tengah District" is to find out how the process of managing bracelet cakes as a typical Ranau culinary in Tanjung Baru Village, District Buay Pematang Ribu Central Ranau, South Ogan Komering Ulu Regency. The philosophy is that whoever provides this unique snack at big events or weddings, will get eternity, blessings, and sweetness in life. The ring cake symbolizes a bond or eternity as a hope for the future life of the bride and groom.